Trends and Challenges in Communication Research: Searching for the Fresh Insights to Understand the Vibrant of Communication Phenomenon - Hermin Indah Wahyuni (The Indonesian Journal of Communication Studies, 2009)
This paper examines the research development in communication as social science. It is done through the analysis of three trends. They include trends of society as context for the development of communication studies; trends for the developing theory of communication studies; and trends in methodology issues. The meanings of 'communication' are complex and vary with the field it is being used, whether this is media and communication studies, cybernetics, information technology studies, or psychology, and so any definition is merely a beginning of the process of understanding the term. Along with intertwine of communication studies with other social sciences; the development of research in communication studies faces an interesting dynamic, trends and challenges. Keywords: communication, theory and methodology